Capability for Exploration Students in Statistical Literacy: A Case of Quantitative Reasoning - Guntur, Mochamad; Retta, Allen Marga; Andriani, Nining; Siregar, Pariang Sonag (Mandalika Mathematics and Educations Journal, 2025)
Statistics is often considered a challenging subject, where high levels of anxiety can hinder understanding of the material, affect results, and hinder the development of statistical skills. This study aims to analyze effectiveness of four learning strategies namely tutorial learning, presenter learning, project online learning, and project face to face learning in improving students' statistical literacy skills. This study used a quantitative approach with a posttest group design research design involving 140 students who were divided into four treatment groups. The analysis technique used is MANOVA (Multivariate Analysis of Variance) with the stages of normality test, homogeneity, multiple comparisons, and Tukey HSD further test. The results show that Tutorial Learning, Presenter Learning, and Project Face to Face Learning strategies have a more significant impact on improving statistical literacy. The three strategies showed relatively balanced effectiveness in improving students' statistical skills. This finding confirms the importance of selecting appropriate learning strategies to promote a deep and meaningful understanding of statistics. This research provides an empirical contribution to the development and selection of appropriate learning strategies, especially in statistics education at the tertiary level. It also recommends further exploration of innovative, contextual, and adaptive combinations of learning strategies to students' needs.